FIKIH GOLONGAN INGKAR HADIS - Abbas Langaji (Universitas Islam Negeri Jakarta, 2014)
The Fiqh of Reject Hadis Group. Since the classic time up to nowdays, the Islamic fiqh form always uses Qur’an and Hadis as normative sources. The appearance of community who denied the authority of Prophet Muhammad Saw. through his Hadis in deciding a law creates a new form in “fiqh” which is ephistemologically implies not only to the exixtance of a different Islam but also and odd Islamic fiqh. It is believed that the separation of Hadis and Qur’an in deciding a law will cause confusion and ambivalence attitude for the believers.DOI: 10.15408/ajis.v14i2.1282